Clinical Pharmacology‐Driven Translational Research to Optimize Bedside Therapeutics of Sotalol Therapy - Elyes Dahmane; Kathy Tang; Jogarao V.S. Gobburu; T. Joseph Mattingly II; Brent N. Reed; Vincent Y. See; Joshuha Ayres; Vijay Ivaturi (Wiley, 2019)
Oral sotalol, used in adults for sinus rhythm control, is initiated at 80 mg b.i.d. and titrated to a maximum safe dose. The US Food and Drug Administration recommends monitoring the corrected QT interval (QTc) for at least 3 days, until steady‐state exposure of the drug is reached, before patient discharge, which can significantly impact the total cost of treatment. The objectives of this research were to design an accelerated intravenous sotalol loading and maintenance therapy that will reduce the hospital length of stay and to also evaluate the pharmacoeconomic impact in a hospital setting. Pharmacokinetic simulations of sotalol plasma concentrations vs. times profiles were performed to determine the optimal intravenous/oral transition regimen. A cost minimization analysis from the health sector perspective was conducted to assess the cost savings for these proposed accelerated regimens. For a chosen target dose of 120 mg b.i.d., two infusions of 40 mg over 1 hour and 20 mg over 0.5 hour, each followed up by an evaluation of QTc, can be administered followed immediately by the target oral maintenance dose of 120 mg at the end of the second infusion. Consequently, steady‐state exposure and, therefore, steady‐state QTc are obtained on the first day of therapy, facilitating an earlier hospital discharge. Two and 1‐day mean total cost of −$3,123 (95% confidence interval (CI), −$3,640, −$2,607) −$4,820 (95% CI, −$5,352, −$4,288) were observed for this strategy, respectively. We are proposing an intravenous to oral transition strategy for sotalol that has the potential to significantly reduce cost and increase patient convenience.